Save, Spend or Give? A Model of Housing, Family Insurance, and Savings in Old Age - Sean Fahle; Daniel Barczyk; Matthias Kredler (ZBW - Leibniz Information Centre for Economics, 2021)
Housing and family are prominent aspects of old age, but how they shape the elderly's savings, spending, and inter-generational transfer behavior remains elusive. We develop a dynamic, non-cooperative model of the family with an illiquid housing asset and joint bargaining between elderly parents and their children over the homeownership and care arrangements of the parents. The model reveals important interactions between children, homeownership, and long-term care risk. Most notably, we find that housing plays the role of a commitment device that facilitates informal care arrangements within families and delays the spend-down of parental wealth. These interactions provide useful insights into several patterns in the data: the widely divergent savings behavior of homeowners and renters, the puzzling similarities in the bequests of parents and childless individuals, and the fact that parents withhold most inter-generational transfers until their deaths. The model's novel mechanisms and predictions are consistent with several empirical patterns.
Keywords: D1; 330; consumption/saving/wealth of the elderly; family insurance; inter-generationaltransfers; dynamic game